2013
DOI: 10.1186/2191-0855-3-36
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis natto: a non-toxic source of poly-γ-glutamic acid that could be used as a cryoprotectant for probiotic bacteria

Abstract: It is common practice to freeze dry probiotic bacteria to improve their shelf life. However, the freeze drying process itself can be detrimental to their viability. The viability of probiotics could be maintained if they are administered within a microbially produced biodegradable polymer - poly-γ-glutamic acid (γ-PGA) - matrix. Although the antifreeze activity of γ-PGA is well known, it has not been used for maintaining the viability of probiotic bacteria during freeze drying. The aim of this study was to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 35 publications
(46 reference statements)
5
59
0
Order By: Relevance
“…2(b). During the co-fermentation, the viable cell count of B. subtilis decreased at the beginning, but then increased by the seventh day, during the second fermentation, whereas the viable cell count of L. (Bhat et al, 2013). Therefore, the initial fermentation with B. subtilis was an essential step to provide adequate conditions for the growth of L. plantarum K154, including a thick consistency (anaerobic medium), moderate pH, and low acidity (Kim et al, 2014b;Park et al, 2014).…”
Section: Effect Of the Co-culture On The Production Of Functional Commentioning
confidence: 99%
“…2(b). During the co-fermentation, the viable cell count of B. subtilis decreased at the beginning, but then increased by the seventh day, during the second fermentation, whereas the viable cell count of L. (Bhat et al, 2013). Therefore, the initial fermentation with B. subtilis was an essential step to provide adequate conditions for the growth of L. plantarum K154, including a thick consistency (anaerobic medium), moderate pH, and low acidity (Kim et al, 2014b;Park et al, 2014).…”
Section: Effect Of the Co-culture On The Production Of Functional Commentioning
confidence: 99%
“…The effect of c-PGA on the viability of probiotic bacteria during freeze-drying was investigated by Bhat et al (2013). Results showed that 10 % c-PGA was found to protect …”
Section: Food Applicationsmentioning
confidence: 99%
“…Mitsuiki et al (1998) c-PGA with a molecular mass of 257 kDa has been used as a cryoprotectant for probiotic bacteria to improve their survival during production. Bhat et al (2013) Bitterness-relieving agent c-PGA has been used as a bitterness-relieving agent Sakai et al (2000) A. Ogunleye and others which has been used to effectively treat retinal disorders. These advantages include lack of complications of steroidinduced glaucoma and post-capsular cataract formation.…”
Section: Medical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Taguchi method based on orthogonal arrays can be used to analyze a large number of variables with a few experimental trials (27). In fact, in contrast to other experimental design methods like full factorial, the Taguchi method as a simple and robust technique (21,30,31). Preparation of spores: Evaluation of the purity of the studied strains and their preparation were conducted by the method described by Alebouyeh et al (32).…”
Section: Introductionmentioning
confidence: 99%